Metadata mapping in Tainacan: new functionality for digital museums linked to the Brazilian Institute of Museums - Siqueira, Joyce; Lopes Martins, Dalton; Nunes Medeiros, Vinícius (Advanced Notes in Information Science, 2022)
The Brazilian Institute of Museums – Ibram, in partnership with the Federal University of Goiás and the University of Brasília, has been building a new service for searching and retrieving digital objects from federal museum collections, an aggregator of cultural data called Brasiliana Museums. The process for aggregating museological data includes different steps. One of which is essential is mapping metadata from the museums of origin to a single metadata standard, enabling the interoperability of information between museums. Ibram's museums make their collections available through the Tainacan software. Thus, this article presents a new functionality for Tainacan, entitled "Tainacan Mappers IBRAM INBCM", which aims to allow users to map their collections to the descriptive elements proposed by Ibram, listed in the National Inventory of Museum Cultural Assets – INBCM. The research is qualitative, exploratory and descriptive, in the form of a case study. The results presented the script developed using the programming language Hypertext Preprocessor - PHP and its benefits for data aggregation. The new functionality is in use in the Brasiliana Museus prototype. As future works, it is intended to implement more advanced operations, such as transformation, concatenation and division of values.